Cytokine-induced oxidative stress in cardiac inflammation and heart failure—how the ubiquitin proteasome system targets this vicious cycle - Voigt, Antje; Rahnefeld, Anna; Kloetzel, Peter M.; Krüger, Elke (Frontiers in Physiology, 2013)
The ubiquitin proteasome system (UPS) is critical for the regulation of many intracellular processes necessary for cell function and survival. The absolute requirement of the UPS for the maintenance of protein homeostasis and thereby for the regulation of protein quality control is reflected by the fact that deviation of proteasome function from the norm was reported in cardiovascular pathologies. Inflammation is a major factor contributing to cardiac pathology. Herein, cytokines induce protein translation and the production of free radicals, thereby challenging the cellular protein equilibrium. Here, we discuss current knowledge on the mechanisms of UPS-functional adaptation in response to oxidative stress in cardiac inflammation. The increasing pool of oxidant-damaged degradation-prone proteins in cardiac pathology accounts for the need for enhanced protein turnover by the UPS. This process is accomplished by an up-regulation of the ubiquitylation machinery and the induction of immunoproteasomes. Thereby, the inflamed heart muscle is cleared from accumulating misfolded proteins. Current advances on immunoproteasome-specific inhibitors in this field question the impact of the proteasome as a therapeutic target in heart failure.